Crystallization and preliminary X-ray diffraction analysis of a eumenine mastoparan toxin: a new class of mast-cell degranulating peptide in the wasp venom - Canduri, F.; Delatorre, P.; Fadel, V; Lorenzi, CCB; Pereira, J. H.; Olivieri, JR; Neto, JR; Konno, K.; Palma, Mario Sergio [UNESP]; Yamane, T.; de Azevedo, W. F. (Munksgaard Int Publ Ltd, 2000)
Mastoparans are tetradecapeptides found to be the major component of vespid venoms. A mastoparan toxin isolated from the venom of Anterhynchium flavomarginatum micado has been crystallized and X-ray diffraction data collected to 2.7 Angstrom resolution using a synchrotron-radiation source. Crystals were determined to belong to the space group P6(2)22 (P6(4)22). This is the first mastoparan to be crystallized and will provide further insights into the conformational significance of mastoparan toxins with respect to their potency and activity in G-protein regulation.